A characterization and perturbation bounds for the weighted core-ep inverse. Issue 7 (3rd August 2020) - Ma, Haifeng
Abstract: In this paper, we present a new characterization of the weighted core-EP inverse of a rectangular matrix. We also investigate the perturbation bounds and approximations for the weighted core-EP inverse.